2007
DOI: 10.1111/j.1551-2916.2007.01774.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Fatigue Crack Growth in Three‐Point Bending PZT Ceramics under Electromechanical Loading

Abstract: This paper investigates experimentally and analytically the cyclic fatigue crack growth in piezoelectric ceramics under electromechanical loading. Cyclic crack growth tests were conducted on lead zirconate titanate (PZT) ceramics subjected to dc electric fields, and a finite element analysis was used to calculate the maximum energy release rate for the permeable crack model. Based on bending experiments using single‐edge precracked‐beam specimens, cyclic fatigue crack growth rates are found to be sensitive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Shindo et al 1 performed an experimental and analytical study on the static fatigue of the PZT ceramics under electromechanical loading, and showed that direct current (DC) electric fields can affect the fatigue life of the PZT ceramics. Narita et al 2 also studied the cyclic fatigue crack growth in single-edge precracked-beam (SEPB) PZT specimens under sinusoidal mechanical load and DC electric fields, and discussed the effect of applied electric fields on the crack * Corresponding author. Tel.…”
Section: Introductionmentioning
confidence: 99%
“…Shindo et al 1 performed an experimental and analytical study on the static fatigue of the PZT ceramics under electromechanical loading, and showed that direct current (DC) electric fields can affect the fatigue life of the PZT ceramics. Narita et al 2 also studied the cyclic fatigue crack growth in single-edge precracked-beam (SEPB) PZT specimens under sinusoidal mechanical load and DC electric fields, and discussed the effect of applied electric fields on the crack * Corresponding author. Tel.…”
Section: Introductionmentioning
confidence: 99%
“…4 one obtains the T-stress as a function of the applied electric field. Superposition of this result with the mechanically induced T-stress (12), as anticipated in (11), would yield the variation of T-stress under coupled electromechanical loading. The final results, in conjunction with the experimental data reported in Figure 2, are plotted in Figure 6.…”
Section: T-stress and Crack Path Stabilitymentioning
confidence: 84%
“…In these services, ferroelectrics have to bear external electrical and/or mechanical loadings in a cyclic or a static form. Crack growth in ferroelectrics driven by electrical or mechanical, or electromechanical loading has been an important topic in the past two decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. For details, one can refer to the monograph by Yang [15] and the review by Schneider [16].…”
Section: Introductionmentioning
confidence: 99%
“…The discussion has focused on the fatigue of PZT ceramics, [167] and static, [168] dynamic, [169] and cyclic [170] fatigue of PZT ceramics with a crack under a DC electric field. Significant research has also been conducted on the fatigue crack behavior in piezoelectric ceramics.…”
Section: Electromagnetic Fatigue Crack Behaviormentioning
confidence: 99%